Deep Brain Stimulation of the Subthalamic Nucleus Modulates Reward-Related Behavior: A Systematic Review - Vachez, Yvan M.; Creed, Meaghan C. (Frontiers in Human Neuroscience, 2020)
Deep brain stimulation of the subthalamic nucleus (STN-DBS) is an effective treatment for the motor symptoms of Parkinson’s Disease (PD). Despite its unquestioned therapeutic benefits, STN-DBS has been associated with adverse effects on mood and cognition. Apathy in particular, defined as a loss of motivation, has been reported to emerge or to worsen following STN-DBS. However, in most cases it is impossible to disentangle the effects of STN-DBS per se from concurrent reduction of dopamine replacement therapy, from underlying PD pathology or from disease progression. To this end, preclinical models allow for the dissociation of each of these factors, and to establish neural substrates underlying the emergence of motivational symptoms following STN-DBS. Here, we performed a systematic analysis of rodent studies assessing the effects of STN-DBS on reward seeking, reward motivation and reward consumption across a variety of behavioral paradigms. We find that STN-DBS decreases reward seeking in the majority of experiments, and we outline how design of the behavioral task and DBS parameters can influence experimental outcomes. While an early hypothesis posited that DBS acts as a ‘functional lesion’, an analysis of lesions and inhibition of the STN revealed no consistent pattern on reward-related behavior. Thus, we discuss alternative mechanisms that could contribute to these effects, and emphasize that optogenetic-assisted circuit dissection could yield important insight into the effects of the STN on motivated behavior in health and disease. This insight will be critical for understanding and optimizing the application of STN-DBS for the treatment of PD symptoms and for expanding indications, such as obsessive-compulsive disorder or addiction.